TINGKAH LAKU SEKSUAL PEJANTAN SAPI BALI PADA USAHA KAUNG BALI DI DESA MENANGA KECAMATAN RENDANG KABUPATEN KARANGASEM (Sexual behavior of bali bull at kaung bali business in Menanga Village, Rendang District, Karangasem Regency - Puspa Yoga, I Wayan; Sumardani, Ni Luh Gde; Oka, Anak Agung (Universitas Nusa Cendana, 2024)
Sexual behavior of Bali bulls can be expose of libido. The aim of this study was to determine the differences in sexual behavior of Bali bulls with different ages in Kaung Bali Business. The study was conducted for 2 months, from August to September 2023 at the Kaung Bali Business located in Banjar Tegenan, Menanga Village, Rendang District, Karangasem Regency, Bali Province. The design used in this study was a Completely Randomized Design (CRD) with 3 treatments and 4 replications. Treatment 1 (T1) I2 Bali bulls (2-3 years old), treatment 2 (T2) I3 Bali bulls (3-4 years old), and treatment 3 (T3) I4 Bali bulls (> 4 years old). Each treatment was repeated 4 times and each replication consisted of 1 Bali bull. The variables observed in this study were sexual behavior, namely the length of time making out, the duration of appearance of flehmen, the length of libido, and the time of ejaculation. The results showed that the length of making out (second) T1 (41.00), T2 (21.75), and T3 (30.00); the duration of appearance of flehmen (second) T1 (21.75), T2 (9.75), T3 (16.00); the length of libido (second) T1 (41.00), T2 (21.50), T3 (30.00); and the ejaculation time (second) T1 (54.25), T2 (43.00), T3 (52.50); each variable showed significantly different results (P<0,05). The conclusion of this research is the sexual behavior of Bali bull males at the age of 3-4 years or (I3) with a time of making out of 21.50 seconds, a time of onset of flehmen of 9.75 seconds, a time of libido of 21.50 seconds, and a time of ejaculation of 43.00. second. Showed the best results, and this means that age influences the sexual behavior of Bali bull.